Baboon, framework conducido por red de Petri para sistemas reactivos dirigidos por eventos - Rabinovich, Ariel Iván (2019)
Ensuring that a concurrent program is correct means that during its execution no thread suffers starvation, no set of threads falls into a deadlock and their successive states lead to the solution. To assert this, it is necessary to appeal to formal methods. This paper proposes using a Petri Net as the logic of a reactive system, and its execution within a framework based on a concurrency monitor. It is put forward that the logical execution flow of the implemented system is driven by the execution of the model. Thus, the model transfers its properties to the system, which has been verified.